PENGARUH STORE ATMOSFER TERHADAP KEPUTUSAN PEMBELIAN DI MEZZO COFFE & BISTRO KENDARI - Titop, Herman; Manggau, Richar Heser; ., Safuruddin (Fakultas Ekonomi Dan Bisnis Universitas Sulawesi Tenggara, 2020)
This study aims to to know and to analyze do store the atmosphere influential of the decision purchases inMezzo Coffe& Bistro Kendari. Types of data in this research is primary data.The subject of this research is 20 samples of people are customersMezzo Coffe& Bistro Kendari. Data was gathered using a questionnaire.The data collected is processed using software application spss.This study using simple linear regression analysis and tests partial ( t ). The results of the study in full shows that store the atmosphere have had a positive impact of the decision of purchases inMezzo Coffe& Bistro Kendari.